Report : Community Network Forum : Enhancing Resiliency to Overcome the Challenges of Work and Personal Stress - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
A forum on approaches to promoting resilience to turn strengths into strategies to restore abilities to cope and adapt to stress in work and personal situations for ourselves and the communities we serve.

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
Number of pages: 8

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)
Number of pages: 6